Sex-specific patterns and lifetime risk of multimorbidity in the general population: a 23-year prospective cohort study - Velek, Premysl; Luik, Annemarie I.; Brusselle, Guy G. O.; Stricker, Bruno Ch; Bindels, Patrick J. E.; Kavousi, Maryam; Kieboom, Brenda C. T.; Voortman, Trudy; Ruiter, Rikje; Ikram, M. Arfan; Ikram, M. Kamran; de Schepper, Evelien I. T.; et al. (BMC medicine, 2022)
Background Multimorbidity poses a major challenge for care coordination. However, data on what non-communicable diseases lead to multimorbidity, and whether the lifetime risk differs between men and women are lacking. We determined sex-specific differences in multimorbidity patterns and estimated sex-specific lifetime risk of multimorbidity in the general population. Methods We followed 6,094 participants from the Rotterdam Study aged 45 years and older for the occurrence of ten diseases (cancer, coronary heart disease, stroke, chronic obstructive pulmonary disease, depression, diabetes, dementia, asthma, heart failure, parkinsonism). We visualised participants’ trajectories from a single disease to multimorbidity and the most frequent combinations of diseases. We calculated sex-specific lifetime risk of multimorbidity, considering multimorbidity involving only somatic diseases (1) affecting the same organ system, (2) affecting different organ systems, and (3) multimorbidity involving depression. Results Over the follow-up period (1993–2016, median years of follow-up 9.2), we observed 6334 disease events. Of the study population, 10.3% had three or more diseases, and 27.9% had two or more diseases. The most frequent pair of co-occurring diseases among men was COPD and cancer (12.5% of participants with multimorbidity), the most frequent pair of diseases among women was depression and dementia (14.9%). The lifetime risk of multimorbidity was similar among men (66.0%, 95% CI: 63.2–68.8%) and women (65.1%, 95% CI: 62.5–67.7%), yet the risk of multimorbidity with depression was higher for women (30.9%, 95% CI: 28.4–33.5%, vs. 17.5%, 95% CI: 15.2–20.1%). The risk of multimorbidity with two diseases affecting the same organ is relatively low for both sexes (4.2% (95% CI: 3.2–5.5%) for men and 4.5% (95% CI: 3.5–5.7%) for women). Conclusions Two thirds of people over 45 will develop multimorbidity in their remaining lifetime, with women at nearly double the risk of multimorbidity involving depression than men. These findings call for programmes of integrated care to consider sex-specific differences to ensure men and women are served equally.